Islamic Philanthropy Model Based on a Waste Bank for Empowering Pesantren Communities: Evidence from Tebuireng Pesantren, Indonesia - Bakhrul Huda; Mochammad Andre Agustianto; Mohammad Majduddin; Abdul Hakim (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2026)
This study examines the development of an Islamic philanthropy model based on a waste bank system in the context of pesantren-based community empowerment. While previous studies have largely positioned waste banks within environmental management and economic empowerment frameworks, they have given limited attention to their potential role as mechanisms of Islamic social finance. This study addresses this gap by analyzing how economic activities derived from waste management can be transformed into socially oriented philanthropic practices. Using a qualitative approach with an intrinsic case study design, this research was conducted at the Tebuireng Waste Bank (BST), Jombang. Data were collected through in-depth interviews, participant observation, and document analysis involving waste bank managers, pesantren authorities, community participants, and beneficiaries. The data were analyzed using thematic analysis to identify patterns and construct a conceptual model. The findings reveal that BST operates beyond a conventional waste management system by integrating circular economy practices with pesantren values, enabling the transformation of economic value into social value. The proceeds from waste-related activities are collectively managed and implicitly function as a form of productive charity, contributing to social redistribution and community empowerment. This process is mediated by the pesantren's institutional and normative roles, ensuring alignment with Islamic principles such as trustworthiness, justice, and public benefit. This study proposes a conceptual model of Islamic philanthropy grounded in a circular economy framework, in which community participation, economic value creation, and social redistribution are interconnected in a sustainable cycle. The study contributes to the literature by extending the scope of Islamic philanthropy beyond traditional instruments toward community-based and productive practices. It also offers practical insights for developing sustainable empowerment models within Islamic social institutions.